2022
DOI: 10.1101/2022.04.20.22274087
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Topographical differences in white matter hyperintensity burden and cognition in aging, MCI, and AD

Abstract: BackgroundWhite matter hyperintensities (WMHs) are pathological changes that develop with increased age and are associated with cognitive decline. Most research on WMHs has neglected to examine regional differences and instead focuses on using a whole-brain approach. This study examined regional WMH differences between normal controls (NCs), people with mild cognitive impairment (MCI), and Alzheimer’s disease (AD). Another goal was to examine whether WMH burden was associated with declines in different cogniti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…With respect to executive functioning, males had a less steep slope in parietal and occipital regions, indicating less cognitive change in those regions associated with WMHs. Previous research also observed that WMHs are associated with change in memory performance in NCs, MCI, and AD 44 . Similarly, we observed that lower memory performance (i.e., high scores in RAVLT percent forgetting, and low scores in RAVLT immediate and learning) was associated with increased WMH accumulation in females.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…With respect to executive functioning, males had a less steep slope in parietal and occipital regions, indicating less cognitive change in those regions associated with WMHs. Previous research also observed that WMHs are associated with change in memory performance in NCs, MCI, and AD 44 . Similarly, we observed that lower memory performance (i.e., high scores in RAVLT percent forgetting, and low scores in RAVLT immediate and learning) was associated with increased WMH accumulation in females.…”
Section: Discussionsupporting
confidence: 85%
“…For the purposes of the current study, specific cognitive tests were chosen to examine multiple cognitive domains known to be associated with WMHs. Global cognition, 41,42 executive functioning, 42,43 memory, 44 and functional status 15 have all been previously observed to be associated with WMH burden. For those reasons, we examined the relationship between WMHs and global cognition (CDR‐SB), executive functioning (Trail‐Making Test Part B [TMT‐B]), Rey Auditory Verbal Learning Test (RAVLT), and functional status in abilities to complete activities of daily living (Functional Activities Questionnaire [FAQ]).…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…WMHs are used as a proxy for cerebrovascular disease, a known contributor for cognitive decline and dementia (Abraham et al, 2016; Tamura & Araki, 2015; Van Der Flier et al, 2018). High WMH burden is associated with increased cognitive decline in MCI (Hirao et al, 2021; Kamal et al, 2022; Kim et al, 2015; Li et al, 2016) and increased rate of progression from MCI to dementia (Dadar et al, 2019). When observing pMCI in Parkinson’s disease (PD) dementia, people with PD-MCI who progressed to Parkinson’s disease dementia, at least 24 months later, had higher WMH volumes compared to PD-sMCI (Sunwoo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%